2006
DOI: 10.1126/science.1128115
|View full text |Cite
|
Sign up to set email alerts
|

High Gamma Power Is Phase-Locked to Theta Oscillations in Human Neocortex

Abstract: We observed robust coupling between the high-and low-frequency bands of ongoing electrical activity in the human brain. In particular, the phase of the low-frequency theta (4 to 8 hertz) rhythm modulates power in the high gamma (80 to 150 hertz) band of the electrocorticogram, with stronger modulation occurring at higher theta amplitudes. Furthermore, different behavioral tasks evoke distinct patterns of theta/high gamma coupling across the cortex. The results indicate that transient coupling between low-and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

128
2,380
6
9

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 2,429 publications
(2,523 citation statements)
references
References 29 publications
128
2,380
6
9
Order By: Relevance
“…4) show similarities in the widespread activity. c band activity is modulated by the oscillations of h band activity [19]. This spreading of PSDt values in large areas could be related to h and low c band coupling.…”
Section: Resultsmentioning
confidence: 95%
“…4) show similarities in the widespread activity. c band activity is modulated by the oscillations of h band activity [19]. This spreading of PSDt values in large areas could be related to h and low c band coupling.…”
Section: Resultsmentioning
confidence: 95%
“…In addition, the sign of the correlation between theta power and BOLD might differ between brain regions. For instance, in intracranial recordings in humans, Canolty et al (2006) found a strong modulation of theta activity on gamma oscillations, but also reported a positive amplitude correlation between the two rhythms. Since gamma is demonstrated to correlate positively with BOLD (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The neuroelectric architecture of the phenomenon appears related to the activity and desynchronization of the theta and alpha frequency bands. These activation patterns also may reflect the effects of gamma band signals (Canolty et al, 2006). It is notable in this context that theta and alpha frequencies have been strongly linked to meditation effects-a self-induced neuroelectric inhibition (Cahn and Polich, 2006).…”
Section: Summary: P300 and Neuroinhibitionmentioning
confidence: 98%